Effect of Storage Period on the Health of Selected Eggs of Domestic Birds in Bayelsa State, Nigeria. (Cigarskruie: Journal of Educational and Islamic Research, 2024)
The marketing of eggs must follow a standard that will check production and storage against the expiration date. There is a need to evaluate the storage period and the health of the eggs of domestic birds from different poultry farms in Bayelsa State, Nigeria. A total of 135 eggs were collected aseptically, 3 each from 5 domestic birds on 3 different poultry farms. These eggs were collected on different storage days (1–7, 8–14, and 15–21) and weighed to ensure their healthy nature. The weight of the different eggs was weighed with an electronic weighing balance and compared among storage days. The result showed that the weight of eggs collected from days 1–7 recorded a mean value, ranging from 54.5±1.0–70.6±0.7g for the whole egg, 27.0±0.6–37.5±0.9g for albumin, 20.1±1.2–24.7±0.3g for egg York, and 5.4±0.3–11.2±0.9g for egg shell. For days 8–14, the weight ranged from 48.8±0.4–64.1±0.4g for the whole egg, 24.4±0.1–33.0±1.1g for albumin, 18.2±0.5–24.3±0.3g for egg York, and 6.0±0.2–9.5±0.4g for egg shell.  The weight of eggs recorded for days 15–21 ranges from 43.5±0.6–60.6±0.9g for the whole egg, 20.8±0.6–30.5±0.8g for albumin, 16.3±0.6–23.6±0.7g for egg yolk, and 5.3±0.1–8.9±0.1g for egg shell. The effects of egg weight and qualities do not significantly decrease within days 1–7, but dramatically decrease from days 8–14 and days 15–21 of storage. The weight of eggs increases with egg size and decreases with an increase in storage period.